Comprehensive analysis of trends in Medicare utilization and reimbursement in Physical Medicine & Rehabilitation: 2012 to 2017. Issue 10 (21st September 2021) - Han, Alex; Carayannopoulos, Alexios G.
Abstract: Introduction: There is an absence of literature describing Medicare utilization by physiatrists, despite their key role in treating Medicare enrollees with qualifying disabilities and common neuromusculoskeletal conditions. Objective: To analyze Medicare data regarding physiatrists and their beneficiaries, services, and reimbursement, as well as trends in utilization and geographic distribution. Design and Setting: Retrospective analysis of publicly available Centers for Medicare & Medicaid Services data for Medicare beneficiaries receiving physiatric services from 2012 to 2017. Main Outcome Measures: After adjustment for inflation, variables assessed for changes over time included provider and beneficiary demographics, total Medicare reimbursement, and the number of services provided, subsequently separated by drug and medical service metrics. Lorenz curves and Gini coefficients were computed to study reimbursement inequality. Choropleth maps were generated to assess geographic differences in physician density and reimbursement, both by state and ZIP code. Results: The number of physiatrists utilizing Medicare increased from 7230 to 7895 from 2012 to 2017, whereas the average number of unique beneficiaries per clinician remained constant (307 vs. 310; p = .51). The beneficiaries' mean hierarchical conditions category (HCC) health risk score, normalized to 1.0 for the average beneficiary, increased significantly from 2012 to 2017 (1.72 vs. 1.80; p < .01). The mean Medicare reimbursement per physiatrist decreased significantly from 2012 to 2017 (131, 960 vs. 117, 623; p < .001), whereas the mean number of services remained constant (3243 vs. 3077; p = .132). Botulinum toxin and baclofen injections were the two most reimbursed drug‐related services. Gini coefficients ranged from 0.52 to 0.53 for 2012 to 2017, suggesting moderate reimbursement inequality, with the 75th percentile receiving on average two times the median. Both physician density and top earners were concentrated in urban and metropolitan areas. Conclusions: Despite rising health care costs and the increasing medical complexity of physiatrists' beneficiaries, Medicare payments have decreased over time. These trends are relevant to both providers and policymakers, particularly in light of unequal geographic distribution of physiatrists across the country.